Variety of Rice Paddy Growth Characters in Various Regions in Banyumas - Risqa Naila Khusna Syarifah; Agus Suroto; Dina Istiqomah; Ida Widiyawati (Nusantara Science and Technology Proceedings, 2021)
This study aims to determine the distribution of rice plant growth characters in various areas in Banyumas Regency. The research took place from February to August 2021 in all sub-districts of Banyumas Regency. The design used was a completely randomized design (CRD) with 5 replications. The factor tested is the difference in location in the sub-district in Banyumas Regency. The variables observed included the character of rice plant growth (plant height, number of tillers, leaf length and leaf width. The results showed that plant height, number of tillers, leaf length and width showed significantly different results between locations (districts) in Banyumas Regency. Height The best plants, leaf length and leaf width were shown in rice plants in Gumelar District, while the highest number of tillers was shown by rice plants in Pekuncen District.